Elliott and QuinnÊ¹s criminal law - Taylor, Louise (New York: Pearson Education Limited, 2018)
Elements of a crime; Strict liability; Murder; Voluntary manslaughter; Involuntary manslaughter -- Non-fatal offences against the person; Sexual offences ; Non-fraudulent property offences ; Fraudulent property offences ; Inchoate offences ; Accomplices ; Corporate liability ; General defences.